Lucky Star Based on a Story by Tristram Tupper - Caliendo, Christopher; Tupper, Tristram (Frank Borzage - Volume Two, 2009)
Frank Borzage, the sensitive actor-turned-director famed for his mystical romanticism created some of Hollywood's most acclaimed and sensual films. This second BFI Frank Borzage volume brings together two more classics from the period that saw his transition from silent pictures into sound. His sensual masterpiece "Lucky Star" (1929) sees the great romantic screen pairing of Janet Gaynor and Charles Farrell for a third time. The tale of a poverty-stricken girl (and budding crook) who is transformed through her friendship with a wheelchair-bound Great War veteran. The chemistry is palpable, and combine with Borzage's visual techniques to create an ethereally beautiful and delicate result. [bfi.org.uk]